Strategi Koperasi Pertama Jaya dalam Pemberdayaan Aspek Lingkungan - Muhamad Abdul Hamid; Ratna Dewi (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2020)
Environmental empowerment is an effort to build communities in improving environmental resources. Koperasi Pertama Jaya with common goals and long-term goals, to get a healthy and clean environment.This research approach with descriptive study method approach. Data collection techniques are carried out by observation, interview and literature study, so a conclusion can be drawn.The purpose of this study is to find out the methods, factors and results of environmental empowerment conducted by the Koperasi Pertama Jaya at Ciheulang Tonggoh, Ciheulang Village, Ciparay District, Bandung Regency.The theories used in this study are environmental empowerment. Empowerment is an effort to build resources by encouraging, motivating and raising awareness of their potential and striving to develop it.In conclusion the empowerment strategy of the Koperasi Pertama Jaya was focused on education training on environmental empowerment by utilizing food waste. Factors that influence empowerment, members of cooperatives carry out environmental management assisted by other elements by making results, an innovation by utilizing residual goods, thus creating liquid and solid organic fertilizers, animal feed needed by the community. Thus environmental problems can be solved.